Design of a Single Band Microstrip Patch Antenna for 5G Applications - Siri Chandana, R; Sai Deepthi, P; Sriram Teja, D; Veera JayaKrishna, N; Sujatha, M (International Journal of Engineering and Technology, 2018)
This article is about a single band microstrip patch antenna used for the 5G applications. And this antenna is suitable for the millimeter wave frequency. The patch antenna design consists of 2 E shaped slots and 1 H shaped slot. These slots are loaded on the radiating patch with the 50 ohms microstrip feed line. For the simulation purpose, Rogersâ€™s RT5880 dielectric substrate with relative permittivity of 2.2 and loss tangent of 0.0009 is used. The design and simulation of the antenna is done using HFSS (High Frequency Structure Simulator) software. The results are simulated for the parameters Return loss, VSWR, 3D Radiation pattern. The proposed antenna has a return loss of -42.4383 at 59 GHz millimeter wave frequency.Â